2024
DOI: 10.1093/mnras/stae773
|View full text |Cite
|
Sign up to set email alerts
|

Triage of the Gaia DR3 astrometric orbits. II. A census of white dwarfs

S Shahaf,
N Hallakoun,
T Mazeh
et al.

Abstract: The third data release of Gaia was the first to include orbital solutions assuming non-single stars. Here, we apply the astrometric triage technique of Shahaf et al. to identify binary star systems with companions that are not single main-sequence stars. Gaia’s synthetic photometry of these binaries is used to distinguish between systems likely to have white-dwarf companions and those that may be hierarchical triples. The study uncovered a population of nearly 3 200 binaries, characterised by orbital separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 116 publications
0
21
0
Order By: Relevance
“…Based on Gaia DR3 data, Shahaf et al (2023) complied a sample of high-probability class III binary systems consisting of an MS and a compact object. Using Gaia synthetic photometry, calculated based on Gaia's low-resolution BP/ RP spectra, Shahaf et al (2024) identified systems with a significant excess red color to further differentiate between class II hierarchical MS triple systems and binaries with a compact-object companion. While an MS companion(s) is expected to contribute flux in the redder wavelengths, the light contribution of a WD companion to the Gaia band is expected to be negligible (due to the extreme size ratio), unless it is very hot and young; then it contributes to the bluer end of the spectrum (see Shahaf et al 2024 for details).…”
Section: < mentioning
confidence: 99%
See 4 more Smart Citations
“…Based on Gaia DR3 data, Shahaf et al (2023) complied a sample of high-probability class III binary systems consisting of an MS and a compact object. Using Gaia synthetic photometry, calculated based on Gaia's low-resolution BP/ RP spectra, Shahaf et al (2024) identified systems with a significant excess red color to further differentiate between class II hierarchical MS triple systems and binaries with a compact-object companion. While an MS companion(s) is expected to contribute flux in the redder wavelengths, the light contribution of a WD companion to the Gaia band is expected to be negligible (due to the extreme size ratio), unless it is very hot and young; then it contributes to the bluer end of the spectrum (see Shahaf et al 2024 for details).…”
Section: < mentioning
confidence: 99%
“…The orbital separations of these systems, on the order of 1 au, place them in a largely unexplored region of parameter space, with only a few such systems known previously (Anguiano et al 2022; Parsons et al 2023). In addition, these systems are not easily reproduced by standard binary population synthesis codes (see discussion in Shahaf et al 2024).…”
Section: < mentioning
confidence: 99%
See 3 more Smart Citations